'A virtuous industry': the agrarian work-family ethic in US rulemaking on child agricultural labour. Issue 6 (18th August 2022) - Reid-Musson, Emily; Strauss, Kendra; Mechler, Meaghan
ABSTRACT: US rules on child agricultural labour have remained largely unchanged since the 1960s. In 2011, the U.S. Department of Labour (DOL) announced a rulemaking proposal to limit child farm labour, especially for migrant children. Yet by 2012, the DOL abandoned its proposed changes following heavy opposition. Based on a random sample and grounded thematic analysis of public submissions to the 2011 rulemaking proposal, our research explores how meanings of work and family surfaced in submissions from rural constituents. Linking Kathi Weeks' feminist critique of the work and family ethic to the agrarian geographical imaginary, we identify how family farm operations were conceived as a locus for the making of 'good' American workers and national (white, settler) citizens. Our analysis explores the ideological function of these 'regressive solidarities' – internalized expressions and experiences of the agrarian work-family ethic – in relation to historical and contemporary unfreedoms embedded in North American food systems.